First records of two large pelagic fishes in the Red Sea: wahoo (Acanthocybium solandri) and striped marlin (Kajikia audax). (1st November 2022) - Williams, Collin T.; Arostegui, Martin C.; Braun, Camrin D.; Gaube, Peter; Shriem, Marwan; Berumen, Michael L.
Abstract: This report provides the first confirmed identifications of wahoo ( Acanthocybium solandri ) and striped marlin ( Kajikia audax ) in the Red Sea, expanding the known ranges of these species into the basin. Potential mechanisms responsible for the lack of regional documentation of the two species are further discussed. These findings illustrate the need for systematic biodiversity surveys of pelagic fish assemblages in the Red Sea.